Starch morphological, structural, pasting, and thermal properties of waxy maize under different heat stress durations at grain formation stage. (15th March 2022) - Gu, Xiaotian; Yang, Siling; Li, Guanghao; Lu, Weiping; Lu, Dalei
Abstract: Heat stress (HS) is a major environmental constraint in sustaining global waxy maize production under future climate condition. Starch physicochemical properties under 5‐day (HS5) and 10‐day (HS10) postsilking HS were investigated using two waxy maize hybrids (Suyunuo5 and Yunuo7) as materials. Ambient and high temperatures were 28°C/20℃ and 35°C/27℃, respectively. Starch granules were enlarged and exhibited additional pitting or cellular structures, increased amylopectin chain length, increased relative crystallinity, and increased 1047/1022 cm −1 ratio under HS. This finding indicated the stable and ordered structure of starch granules, especially under HS10. Pasting viscosities of Yunuo7 reduced by HS, and the change was the same under both HS5 and HS10. Peak viscosity of Suyunuo5 was unaffected and breakdown viscosity increased with HS5 although both characteristics decreased with HS10. HS increased gelatinization temperatures and retrogradation percentage. Results showed that HS enlarges starch granules with stable structure, reduces starch viscosities, and increases retrograde tendency, with severe detrimental effect under long HS durations. Abstract : Starch granules under heat stress were large and have more pittings. Heat stress increase amylopectin chain length, relative crystallinity, and 1047/1022 cm −1 ratio. Past viscosity and retrogradation percentage were deteriorated by heat stress.